Renovación de la zona denominada “Extensión del centro tradicional de Neiva, como estrategia para mejorar las condiciones urbanas, sociales y ambientales (2023)
The present work deals with the processes of development of the city of Neiva, generated by the transformations of the elements of the urban, economic, environmental and social structure of the place, caused by different historical events, such as the emergence of urban growth centers on the outskirts of the city, the lack of implementation and use of land, the generation of new centralities and the displacement of the city center as the structuring axis of the city, which has an urban structure that is deteriorated with spatial and social segregation.